2002
DOI: 10.1103/physrevb.65.245405
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution of the fivefold surface ofiAlPdMnquasicrystals

Abstract: Morphology of the fivefold symmetric quasicrystal surface of AlPdMn was investigated by x-ray reflectivity and by x-ray diffraction. X-ray experiments revealed two different morphologies depending on the surface preparation. Sputtering and annealing up to 900 K, under UHV conditions, produced a rough and facetted quasicrystal surface. These features were confirmed by atomic force microscopy and scanning tunnel microscopy measurements. We also observed that an annealing above 900 K induces a rapid and irreversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
0
9
2
Order By: Relevance
“…The AFM observations in the present work reveal clearly the cluster nature of the i-AlPdMn QC. However, the size of the clusters observed in this work is different from that reported by others [7,8,10]. For example, Cappello et al [8], observed terraces of about 10 nm in height constructed from the packing of small spheres of about 10 nm in radius.…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…The AFM observations in the present work reveal clearly the cluster nature of the i-AlPdMn QC. However, the size of the clusters observed in this work is different from that reported by others [7,8,10]. For example, Cappello et al [8], observed terraces of about 10 nm in height constructed from the packing of small spheres of about 10 nm in radius.…”
Section: Resultscontrasting
confidence: 71%
“…In view of the fact that the oxide layer on the surface of the i-AlPdMn QC surface is typically less than 2 nm thick see Ref. [8]. we assume that it will not affect the surface morphology observed by either SEM or AFM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This array of surface morphologies includes rough surfaces, 4-9 faceted voids, 10 and smooth ͑to within a few tenths of an angstrom͒ terraces. 6,8,9,[11][12][13][14][15][16] The latter type of structure-flat terraces-is the topic of this paper.…”
Section: Introductionmentioning
confidence: 99%